Ocupar e resistir: sentidos e significados atribuídos por alunos ao movimento de ocupação de uma escola pública paulista - Ribeiro, João Carlos Cassiano (2018)
This study aimed to expand knowledge about the occupations carried out by students of a public school in the state of São Paulo, in the year 2015, after the announcement of the state government about the school reorganization, seeking to understand the meanings and significances that the students attributed to the occupations. The research was done in the city of São Paulo and three students who participated in the occupations were selected. Interviews were conducted with the students, which after transcribed were systematized and analyzed based on the methodological proposal of Aguiar and Ozella (2006, 2013) and Aguiar, Soares and Machado (2015), authors which are linked to the theoretical basis of Socio-Historical Psychology. In order to contribute to the analysis, significance nuclei have been constructed, which allow a closer approximation of the areas of meaning. During the analysis of data, it was verified that the students have in common a family trajectory marked by the inequality. The need to work has contributed to the discontinuation of the parent’s studies. The lack of participation of the students in the discussions by the school and the Department of Education is a factor that contributed to the occupation of the school. They understand the limitations of the achievements they have gained and recognize the complexity of the political struggle in which they were involved. In this way, it is understood that by involving students and reflecting on the established relationships between developed school knowledge and the needs and characteristics of the school community contributed to an improvement in students' learning and development, positively impacting developed citizenship relations in society